Impact of Hierarchical Structures and Formal Rules on Public Policy Implementation Effectiveness in Local Government - Faturahman, Reza; Khalid, Agung; Kamaruddin, Ihsan (Journal Social Civilecial, 2023)
This study examines the influence of bureaucratic structures on public policy outcomes, focusing on key elements such as hierarchical structure, division of labor, formal rules, and impersonal relationships. Using a quantitative approach, data were collected from public sector employees and analyzed to determine how these structural elements contribute to the effectiveness of public policies. The results show that hierarchical structure has a positive correlation with policy outcomes, as it facilitates clearer lines of authority and coordination. The division of labor, while enhancing specialization and expertise, also presents challenges in inter-departmental collaboration, especially for complex policy issues. Formal rules and procedures were found to significantly influence policy outcomes, although their rigid application can lead to bureaucratic red tape that slows down decision-making processes. Additionally, impersonal relationships within bureaucratic organizations, while ensuring neutrality, can hinder effective collaboration with external stakeholders. The findings highlight the ongoing relevance of bureaucratic principles in modern governance while also underscoring the challenges posed by rigid structures and the need for adaptability, especially in the context of digital transformation and global governance. This study contributes to the literature on public administration by providing empirical evidence of how bureaucratic structures shape policy outcomes in contemporary settings.